Quality of Life in Women with Defecatory Dysfunctions: Systematic Review of Questionnaires Validated in the Portuguese Language - Vasconcelos Neto, José Ananias; Vasconcelos, Camila Teixeira Moreira; Karbage, Sara Arcanjo Lino; Farias, Hérdeny Di Cárlly de Almeida Rocha; Machado, Stéffany Gadelha de Macêdo; Saboia, Dayana Maia (Revista Brasileira de Ginecologia e Obstetrícia / RBGO Gynecology and Obstetrics, 2019)
Objective To identify the quality of life (QoL) assessment instruments related to the health of women with fecal incontinence (FI) or anal incontinence (AI).Data Sources Systematic review conducted in the Virtual Health Library (VHL), PubMed and Cochrane Library databases. The descriptors used were: Questionnaire, Questionnaires, Quality of life, validation, validation Studies, anal incontinence, fecal incontinence and constipation. The search was performed between December 26, 2017 and the beginning of January 2018. The limits used were female gender.Selection of Studies Initially, 5,143 articles were obtained in the search. The articles of validation for Portuguese of questionnaires for the evaluation of the impact of FI/AI on the QoL of women were considered eligible.Data Collection The article search was conducted according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyzes (PRISMA) guidelines.Data Synthesis Of the 5,143 articles, only 2 fulfilled the inclusion and exclusion criteria: Fecal Incontinence Quality of Life (FIQL) and the Wexner scale (WS). The FIQL evaluates the QoL related to FI, not covering flatus incontinence. The WS assesses flatus incontinence and the severity of the AI. The WS obtained an interclass correlation coefficient (ICC) of 0.932 and a Cronbach α coefficient > 0.90. The FIQL obtained intraexaminer and interexaminer reproducibility ranging from 0.929 to 0.957 and from 0.944 to 0.969, respectively.Conclusions The WS and the FIQL have satisfactory reliability and validity for use during gynecological consultations.
Keywords: fecal incontinence; quality of life; validation studies; surveys and questionnaires; review